Toxicological effects of pet food ingredients on canine bone marrow‐derived mesenchymal stem cells and enterocyte‐like cells. Issue 2 (14th May 2015) - Ortega, M. T.; Jeffery, B.; Riviere, J. E.; Monteiro‐Riviere, N. A.
Abstract: We developed an in vitro method to assess pet food ingredients safety. Canine bone marrow‐derived mesenchymal stem cells (BMSC) were differentiated into enterocyte‐like cells (ELC) to assess toxicity in cells representing similar patterns of exposure in vivo . The toxicological profile of clove leave oil, eugenol, guanosine monophosphate (GMP), GMP + inosine monophosphate, sorbose, ginger root extract, cinnamon bark oil, cinnamaldehyde, thyme oil, thymol and citric acid was assessed in BMSC and ELC. The LC50 for GMP + inosine monophosphate was 59.42 ± 0.90 and 56.7 ± 3.5 mg ml –1 for BMSC and ELC; 56.84 ± 0.95 and 53.66 ± 1.36 mg ml –1 for GMP; 0.02 ± 0.001 and 1.25 ± 0.47 mg ml –1 for citric acid; 0.077 ± 0.002 and 0.037 ± 0.01 mg ml –1 for cinnamaldehyde; 0.002 ± 0.0001 and 0.002 ± 0.0008 mg ml –1 for thymol; 0.080 ± 0.003 and 0.059 ± 0.001 mg ml –1 for thyme oil; 0.111 ± 0.002 and 0.054 ± 0.01 mg ml –1 for cinnamon bark oil; 0.119 ± 0.0004 and 0.099 ± 0.011 mg ml –1 for clove leave oil; 0.04 ± 0.001 and 0.028 ± 0.002 mg ml –1 for eugenol; 2.80 ± 0.11 and 1.75 ± 0.51 mg ml –1 for ginger root extract; > 200 and 116.78 ± 7.35 mg ml –1 for sorbose. Lemon grass oil was evaluated at 0.003–0.9 in BMSC and .03‐0.9 mg ml –1 in ELC and its mechanistic effect was investigated. The gene toxicology studies showed regulation of 61% genes in CYP450 pathway, 37% in cholestasis and 33% in immunotoxicity pathways for BMSC. For ELC, 80% for heat shock response, 69% for beta‐oxidation and 65% for mitochondrial energy metabolism. In conclusion, these studies provide a baseline against which differential toxicity of dietary feed ingredients can be assessed in vitro for direct effects on canine cells and demonstrate differential toxicity in differentiated cells that represent gastrointestinal epithelial cells. Copyright © 2015 John Wiley & Sons, Ltd. Short abstract: Food ingredients clove leave oil, eugenol, guanosine monophosphate (GMP), GMP + inosine monophosphate, sorbose, ginger root extract, cinnamon bark oil, cinnamaldehyde, thyme oil, thymol, lemongrass oil and citric acid showed differential toxicity in canine bone marrow‐derived mesenchymal stem cells, which differentiated into enterocyte‐like cells in vitro . The most toxic ingredients were thymol, eugenol, cinnamon bark oil, cinnamaldehyde, clove leave oil and lemongrass oil (0.002–0.54 mg ml –1 ). GMP, GMP + inosine monophosphate and sorbose were the least toxic ingredients (56.8–116.7 mg ml –1 ).